Paradoxes and prospects of the glocal - Kapustin, Petr (project baikal, 2021)
Globalism has demonstrated both its power and helplessness in creating human qualities of the environment. The latter was a matter of architecture, but it has been a victim of a narrowed and reduced model of globalism, a modernist model. Surmounting the crisis that has taken the past half century cannot be considered complete yet. At present, one can see the problems and prospects of new syntheses of the universal and the local, without which it is impossible to imagine the comprehensive future of the planet.
Keywords: global; local; glocal; total; identity; place; Genius loci